Applying Energy-Dispersive X-Ray Fluorescence Analysis to Detect Tungsten Inclusions in Nuclear Fuel Rod End Plug TIG Welds - Gu, Runqiu; Cheng, Jianfeng; Lai, Wanchang; Wang, Guangxi (Journal of Spectroscopy, 2021)
This study proposes a new method of detecting tungsten inclusions in nuclear fuel rod upper-end plug welds using energy-dispersive X-ray fluorescence (EDXRF) analysis. The Monte Carlo simulation method was used to simulate the process of detecting tungsten inclusions in nuclear fuel rod upper-end plug welds by the EDXRF. The detectable tungsten particle diameters in the zirconium alloy at different depths in welds and the detection limits of the trace tungsten dispersed in welds were obtained. Then, we constructed an experimental device that uses a CdTe detector with an X-ray tube. The results showed that the relative standard deviation of the net count rate of tungsten K-series characteristic X-rays [W (Kα)] was 1.46%, and the optimum parameters are a tube voltage of 150 kV and current of 0.5 mA. These values were used to perform energy-dispersive X-ray fluorescence analysis. These results were compared to the X-ray radiographic results, which were broadly similar. Furthermore, the results of EDXRF analysis were more legible and reliable than those from X-ray radiographic inspections. This study demonstrates the feasibility of applying EDXRF analysis to detect tungsten inclusions.